Why don’t we offer the same help to all victims of cyberbullying? - António, R.; Guerra, R.; Moleiro, C. (The Social Observatory, 2024)
Bullying rarely occurs without an audience and can be considered a group phenomenon, rather than just a personal behaviour. Evidence suggests that previous contact between different social groups increases bystanders’ helping intentions in bullying episodes. However, less is known about the potential positive effects of intergroup factors on bystanders’ behaviours when witnessing cyberbullying based on one’s social identity or group membership. The online survey conducted with 4,507 Portuguese youth as part of the TURN_ON HELP project, which aimed at understanding cyberbullying towards different minority groups, namely LGBTI+ and Black youth, showed that bystanders’ responses varied depending on the target of the cyberbullying, helping an LGBTI+ youth victim less than a Black one. This research can contribute to the development of theoretical approaches for understanding what promotes bystanders’ helping intentions in bias-based cyberbullying episodes, as well as to the development of specific interventions to foster helping behaviours among youth.